Processing of Organic Waste Using Biopori Infiltration Holes (Case Study: Organic Waste at Christian University of Technology Solo) - Elvis Umbu Lolo; Richardus Indra Gunawan; Agerippa Yanuranda Krismani; Yonathan Suryo Pambudi; Cicik Sudaryantingsih; Widianto; Ripi (East Asian Journal of Multidisciplinary Research, 2023)
Christian University of Technology Solo produces quite a large amount of waste, which in 1 day produces around 7 kg of waste resulting from the activities of 2 canteen units, dry leaf waste on the UKTS campus yard, and waste from the activities of students, staff and lecturers at Solo Christian University of Technology. This method uses biopore infiltration holes located in the yard of Solo Christian University of Technology, where organic waste is divided into two groups, namely kitchen waste and dry leaves. Kitchen waste is mixed into one consisting of leftover rice, vegetables, chicken bones, fried leftovers and dry leaves which are cut and crushed into leaf powder. The waste is put in the biopori infiltration hole and given water to keep it moist. Humidity was measured every week and water was added. The results of this study were that from 5 biopori infiltration holes with 4.88 kg of dry leaf waste, 1.48 kg of compost was produced with a decomposition process time of 57 days, while the 6th biopori infiltration hole had the amount of waste. a 6.5 kg kitchen produces 1.3 kg of compost with a decomposition time of 30 days